Managing Hypogonadism in Older Men: Is Testosterone Therapy the Answer? - Jagodzińska, Julita; Grześkowiak, Martyna; Juchniewicz, Agata; Sapikowski, Jakub; Janiszewska, Maria; Kuba, Iga; Idziński, Jakub; Lubomska, Anna (Quality in Sport, 2025)
Introduction: Age-related decline in testosterone production contributes to late-onset hypogonadism (LOH), characterized by reduced muscle mass, bone density, and sexual function. The increasing use of testosterone replacement therapy (TRT) in aging men has raised concerns about its efficacy and safety. This review summarizes current evidence regarding the benefits and risks of TRT in older men. Material and Methods: A literature review was performed in PubMed, Scopus, Cochrane Library, and Web of Science, including studies from 2015–2025. Clinical trials, meta-analyses, and reviews on the effects of TRT on body composition, bone density, metabolic profile, sexual and cognitive function, cardiovascular health, and prostate safety were analyzed. Results: TRT improves lean body mass, reduces visceral fat, and enhances bone mineral density, especially in the lumbar spine. Moderate benefits are seen in sexual desire and erectile function, with no significant cognitive improvement. The most frequent adverse effect is erythrocytosis. Prostate safety appears acceptable when physiological testosterone levels are maintained. Conclusion: TRT can provide functional and metabolic benefits in older hypogonadal men but requires careful selection, individualized dosing, and regular monitoring due to potential hematologic and cardiovascular risks.